Inactivation of anoctamin‐6/Tmem16f, a regulator of phosphatidylserine scrambling in osteoblasts, leads to decreased mineral deposition in skeletal tissues. (15th January 2013) - Ehlen, Harald WA; Chinenkova, Milana; Moser, Markus; Munter, Hans‐Markus; Krause, Yvonne; Gross, Stefanie; Brachvogel, Bent; Wuelling, Manuela; Kornak, Uwe; Vortkamp, Andrea
Abstract: During vertebrate skeletal development, osteoblasts produce a mineralized bone matrix by deposition of hydroxyapatite crystals in the extracellular matrix. Anoctamin6/Tmem16F (Ano6) belongs to a conserved family of transmembrane proteins with chloride channel properties. In addition, Ano6 has been linked to phosphatidylserine (PS) scrambling in the plasma membrane. During skeletogenesis, Ano6 mRNA is expressed in differentiating and mature osteoblasts. Deletion of Ano6 in mice results in reduced skeleton size and skeletal deformities. Molecular analysis revealed that chondrocyte and osteoblast differentiation are not disturbed. However, mutant mice display increased regions of nonmineralized, Ibsp ‐expressing osteoblasts in the periosteum during embryonic development and increased areas of uncalcified osteoid postnatally. In primary Ano6 −/− osteoblasts, mineralization is delayed, indicating a cell autonomous function of Ano6 . Furthermore, we demonstrate that calcium‐dependent PS scrambling is impaired in osteoblasts. Our study is the first to our knowledge to reveal the requirement of Ano6 in PS scrambling in osteoblasts, supporting a function of PS exposure in the deposition of hydroxyapatite. © 2013 American Society for Bone and Mineral Research